The Date of the Stein Manuscript of the Platform Sūtra: Codicological Observations on a Chan Manuscript from Dunhuang - Galambos, Imre (Journal of Chan Buddhism, 2021)
As some of the earliest extant examples of Chan writings survived in the Dunhuang library cave, they have been studied extensively in modern scholarship as witnesses of texts that were to leave a lasting impact throughout East Asia. This paper uses a codicological perspective to re-examine the so-called Stein manuscript of the Platform Sūtra kept at the British Library. This is one of the key sources for the study of early Chan, primarily because it contains what is often claimed to the be the earliest copy of the Platform Sūtra. The paper’s aim is to demonstrate that the manuscript, in its physical reality, can tell us additional information beyond what has already been learned from the text in it. This entails a shift from a focus on the transmission of the text to its use in a concrete setting. On the one hand, the ‘material’ approach can offer insights into the identity and background of the persons and communities involved in copying and using such texts, and on the other, it can help to reassess the accepted dating of the manuscript. Among the key pieces of information not considered before is an ownership note written on the spine of the manuscript, pointing to a connection with educational setting.